2013
DOI: 10.1002/jobm.201200318
|View full text |Cite
|
Sign up to set email alerts
|

Novel arrangement of theblaCTX-M-55gene in anEscherichia coliisolate coproducing 16S rRNA methylase

Abstract: A multi-drug resistant Escherichia coli C21 was isolated from a chicken in China. It was shown to be positive for the presence of the blaTEM-1, blaCTX-M-55 and rmtB genes by PCR. This strain was examined by phylogenetic grouping, conjugation experiments, plasmid analysis, PCR-based replicon typing and multi-locus sequence typed (MLST). The genetic environment of blaCTX-M-55 was investigated by PCR mapping. The strain belonged to phylogroup A, ST156. The blaCTX-M-55 and rmtB genes were found to be present in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
4
19
0
1
Order By: Relevance
“…This finding is therefore consistent with previous reports in that commensal E. coli strains in food animals were likely to be a reservoir of ESBL genes (24) and to play a role in dissemination of such resistance (41). Various other reports also showed that ST156 was detected in water and animals (42)(43)(44). The strong linkage of bla CTX-M-15 ST156 isolates from humans, animals, and the environment warrants further attention to and research on this type of E. coli bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is therefore consistent with previous reports in that commensal E. coli strains in food animals were likely to be a reservoir of ESBL genes (24) and to play a role in dissemination of such resistance (41). Various other reports also showed that ST156 was detected in water and animals (42)(43)(44). The strong linkage of bla CTX-M-15 ST156 isolates from humans, animals, and the environment warrants further attention to and research on this type of E. coli bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…CTX-M-3 was found to be the major CTX-M-1 group ESBL, followed by CTX-M-15 and CTX-M-55. However, previous studies have shown a completely different distribution for CTX-M-1 group beta-lactamases, and CTX-M-55 has already replaced CTX-M-3 as the main concern with regard to antibiotic treatment options for infections in mainland China (7,11,19). The rising proportion of bla CTX-M-55 in our study suggests 2 possibilities.…”
Section: Discussionmentioning
confidence: 46%
“…CTX-M-55 first isolated from E. coli in Thailand [33] developed from one point mutation of CTX-M-15, leading to replacement of amino acid 80.In recent years, CTX-M-55 in E. coli was separated from food animals and pets in China [33][34][35][36][37], but was very rare in clinical isolates. Yu et al [10] first detected it in S. Typhimurium from the stool of a child in 2011.…”
Section: Discussionmentioning
confidence: 99%